“Sustainable Human Capital: How Employee Voice Strengthens Mental Well-Being, Work–Life Integration, and Productive Workplaces.” (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Sustainable Human Capital (SHC) has become central to organizational sustainability, emphasizing the long-term preservation of employees’ health, motivation, and capacity to contribute (Dyllick & Hockerts, 2002). Sustainable human resource management (SHRM) views employees as a very important resource for the organisation, while paying close attention to their preferences, needs, and perspectives. Sustainable Human Capital (SHC) has become a critical priority as organizations seek to build resilient, healthy, and high-capacity workforces. However, existing research has not fully explained how individual-level psychological and motivational processes contribute to long-term human capital sustainability. This conceptual paper proposes an integrative framework in which employee voice serves as a foundational driver that enhances motivation, which in turn strengthens mental well-being, work–life integration, and workplace productivity. Drawing on Sustainable HRM theory, Social Exchange Theory, Job Demand Resource Theory, Stakeholder Theory, and motivation-based perspectives, the model argues that when employees feel able to express ideas and concerns, their intrinsic and extrinsic motivation increases, leading to improved psychological health, reduced stress, greater balance between work and personal life, and higher engagement and performance. These individual outcomes accumulate to form Sustainable Human Capital, characterized by a healthy, motivated, and productive workforce capable of supporting long-term organizational sustainability. The paper concludes that employee voice strengthens sustainable human capital by increasing employee motivation, which enhances mental well-being, work–life integration, and workplace productivity—ultimately creating a healthy, motivated, and future-ready workforce.